Investigating the thermal, physical and mechanical performance of waste wood plastic composite as building construction material - Uka, Szahirrah Joy S. (2020)
Many studies have been conducted related to plastic wastes and optimizing it into a better material. This is to lessen the tons of waste plastic that have become a huge problem around the world. This study was conducted to produce a material from waste plastic and sawdust to aid in this rising problem. Composites can be the better product by having both the properties of the mixed raw materials. The goal is also to perform it by more accessible means that can be integrated in small communities. Melting of plastic can optimize huge amount of waste in one product. PET, HDPE, and Soft Plastics, each of them was mixed with sawdust and are tested to produce a material. Different methods were tried to make a composite product. Among the methods are flat-pressing, melt and mold, and melt and manual press. These methods were tested using accessible means and among them, the only method that produced acceptable material is melt and mold. And among the different mixtures, only HDPE and sawdust mix were produced. Producing the material also causes too much smoke which leads to integration of condensation chamber. In using the chamber, a brownish liquid was made from the process and it needs further research to be tested as fuel. Only the 70:30 and 50:50 HDPE to sawdust wood plastic composite mixtures were produced. Tests were performed and it includes: compressive, flexural, water absorption, thermal property, and costing. All the tests have average to impressive results. More plastic leads to higher compressive and bending strength and lesser water absorption. The more sawdust in the mixture made the material better thermally but it has more water absorption property. Cost of both products were lower from conventional products.